MOTIVASI : PEMEDIASI PADA PENGARUH KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA KANTOR BPJS KETENAGAKERJAAN BALI DENPASAR - Almaulida Yunia Putri; Anak Agung Dwi Widyani; Putu Ayu Sintya Saraswati (JUIMA : JURNAL ILMU MANAJEMEN, 2023)
This study aims to determine the effect of communication on employee performance with motivation as an intervening variable at the Bali Denpasar Employment BPJS Office. The population in this study were employees who worked at the Bali Denpasar Branch of the Employment BPJS Office, a total of 42 people. The sample in this study amounted to 42 people using a non-probability sampling technique with a saturated sample technique. Data analysis technique using SEM-PLS 3.0. The results showed that: Communication has a positive and significant effect on employee motivation and performance. Motivation also has a positive and significant effect on employee performance and motivation acts as an intervening variable on the effect of communication on employee performance.